2015
DOI: 10.3906/biy-1406-81
|View full text |Cite
|
Sign up to set email alerts
|

Biological synthesis of silver nanoparticles and evaluation of antibacterialand antifungal properties of silver and copper nanoparticles

Abstract: There is increasing attention being paid to metallic nanoparticles because of their intensive applications in different areas of science such as medicine, chemistry, agriculture, and biotechnology. In addition, there has been growing interest in using environmentally friendly methods of synthesizing nanoparticles without making or using substances risky to the environment and human health. Biological methods for the synthesis of nanoparticles have been considered as possible ecofriendly alternatives to chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…The obtained results are agreed with the findings of some previous studies. Jafari et al [45] in their research used AgNps with the size of 50 nm and observed inhibitory effect against Penicillium chrysogenum. They found that the particles have the toxicity effects on cytoplasma membrane.…”
Section: Effect Of Nanoparticle Concentrations On Mycelial Weight Andmentioning
confidence: 99%
“…The obtained results are agreed with the findings of some previous studies. Jafari et al [45] in their research used AgNps with the size of 50 nm and observed inhibitory effect against Penicillium chrysogenum. They found that the particles have the toxicity effects on cytoplasma membrane.…”
Section: Effect Of Nanoparticle Concentrations On Mycelial Weight Andmentioning
confidence: 99%
“…Cá v t l u n no ó k t ướ tron k oản từ 1-100 nm đ n t u út s ú ý về n ữn đặ t n k á b t ủ ún v k ả năn ứn dụn uy n sâu tron n ều lĩn v k o n ư dượ p ẩm ó n n n p n n s n .. [4,5]. V áp dụn n n n no v o á n n n n n p v t p ẩm đượ đặt r lần đầu t n tron ươn trìn n độn ủ Bộ N n n p o ỳ v o 9/2003 [6] v đượ d đoán sẽ l n n t en t t o r t y đổ qu n tr n tron á n n n y. Tron n ữn năm đầu t n v áp dụn n n n no tron sản xuất n n n p ủ yếu đượ t n qu á n n ứu tron p òn t n m n ưn n y s u đó nó đã bắt đầu v đ n t ếp tụ ó ản ưởn đán kể tron á lĩn v qu n tr n n ư l t o á n ây trồn mớ p át tr ển v t l u ứ năn mớ v t n p ân p t n m n o ó ất n n n p n ư t u d t ỏ p ân bón v t u trừ sâu t n t n m n o ế b ến t p ẩm b o bì v á lĩn v k á n ư k ắ p ụ u quả ủ dư lượn ất d t ỏ v t u trừ sâu tron t v t v đất tron xử lý nướ t ả quản lý t n uy n t n n n v p át n sớm á mầm b n á ất ây n ễm tron ây trồn v t p ẩm,... [7].…”
Section: đặT Vấn đề unclassified
“…Copper nanoparticles possess many intriguing properties which provide them many applications, such as antibacterial, antifungal, and antiviral applications [16][17][18]. A great deal of work can be found concerning the application of copper nanoparticles in electrochemistry [19,20] and electroanalysis [21].…”
Section: Introductionmentioning
confidence: 99%